New contribution to the family Geometridae from the Philippines and Indonesia, they describe a new genus and four new species. (Lepidoptera: Geometridae, Ennominae, Larentiinae) - Expósito-Hermosa, Andrés (SHILAP Revista de lepidopterología, 2025)
One genus and four new species are described: Tautela Expósito, gen. nov., Tautela stueningi Expósito, sp. nov., Polyclysta schmidtae Expósito, sp. nov. and Eurychoria parallelae Expósito, sp. nov. from Indonesia, as well as Peratostega uniformis Expósito, sp. nov. from the Philippines. Images of the adults as well as the genitalia of the new species are included.